Monetary Policy in the New Normal - Bayoumi, Tamim; Dell'Ariccia, Giovanni; Habermeier, Karl.; Mancini Griffoli, Tommaso (Washington, D.C. : International Monetary Fund, 2014)
The proposed SDN would take stock of the current debate on the shape that monetary policy should take after the crisis. It revisits the pros and cons of expanding the objectives of monetary policy, the merits of turning unconventional policies into conventional ones, how to make monetary policy frameworks more resilient to the risk of being constrained by the zero-lower bound going forward, and the institutional challenges to preserve central bank independence with regards to monetary policy, while allowing adequate government oversight over central banks' new responsibilities. It will draw policy conclusions where consensus has been reached, and highlight the areas where more work is needed to get more granular policy advice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet